A Telescope Takes Flight [NEWS]. - Dumiak, M.
Describes SOFIA - the Stratospheric Observatory For Infrared Astronomy, a powerful flying telescope. An infrared telescope with remarkable spectral range, it picks up the mantle of the Kuiper project. Kuiper was groundbreaking, but SOFIA, seated aft of the wing of a Boeing 747 jumbo jet, has more scope: it will scan the deep heavens, where stars are forming and the universe is still being born. SOFIA flies at 13300 meters, above 99 percent of the atmospheric water vapor that obstructs infrared observation from the ground. A hatch in the plane, which is traveling at 800 kilometers per hour, opens the telescope to the elements; its mirror is 2.7 meters across. Because of its size, SOFIA can carry large, power-intensive instruments and high-resolution spectrometers. That gives astronomers a wavelength range for observation rare in its breadth, from 0.3 micrometers, which is near the visible range, through the far infrared, out to 1600 mum. Infrared telescopes cut through the gases and clouds in the universe that obscure optical observation. Project scientists plan to use the broad spectral range across nine instruments - seven designed in the United States, two in Germany - to explore what powered the luminous galaxies that lit up the early universe, peek into "dark" clouds to take a census of new stars, see near the center of black holes, look at the physical conditions of the universe's infancy, and map out chemical architectures in the interstellar medium. The science instruments and counterweights balance the telescope, and the result is an apparatus that can be aimed and kept still, mostly on account of its own inertia. Torque motors and spherical brakes keep the telescope tracking the desired stellar target, while gyros keep track of the telesope's absolute position. Complicating matters was the 2003 launch of the Spitzer observatory, a space-based infrared telescope that is already producing great results. Critics raised eyebrows at spending so much money to t- urn a jumbo jet into a flying infrared observatory while a space-based infrared telescope was beating it into operation. Citing repeated delays, slipping schedules, and ballooning budgets, NASA announced last year that SOFIA would lose its funding. The project's plans have been stretched before. But with a budget in place, SOFIA is close now.
Keywords: Boeing 747 jumbo jet; NASA program; SOFIA flying infrared telescope; Stratospheric Observatory for Infrared Astronomy; Black holes; Instruments design; Interstellar chemistry; Interstellar medium; Luminous galaxies; Optical observation; Size 2.7 m; Spectrometers; Star formation; Universe physical condition; Wavelength 0.3 mum to 1.6 mm